Who is responsible for construction safety in Australia? A STAMP analysis. (December 2020) - Woolley, Matthew; Goode, Natassia; Salmon, Paul; Read, Gemma
Highlights: The first Australian Construction Control Structure and first application of STAMP in the domain. The structure presents the first network of construction actors, controls and feedback mechanismsmodel presents the first network of construction actors, controls and feedback mechanisms. Coronial inquest findings are analysed to demonstrate the benefit of the new structure for Coroners. The structure provides opportunity for future predictive and retrospective analysis. Construction safety is not the responsibility of one isolated person or entity. Existing system effectiveness feedback mechanisms are progressively limited and less intuitive. Many feedback mechanisms to higher system levels focus on financial and compliance performance. Abstract: Limitations surrounding knowledge of the construction safety operating system have contributed to a failure to understand and prevent fatal incidents. The aim of this paper is to present a control structure model of construction in Australia to provide an improved understanding of the construction operating system. The model was developed by applying and extending the Systems Theoretic and Accident Model and Processes (STAMP) method to show the actors, organisations, controls, communication loops and relationships that are involved in managing safety throughout the Australian construction industry. The control structure was validated by subject matter experts from across all levels of the system. The analysis highlights a disconnect between the upper and lower levels of the system in terms of feedback mechanisms and relationships that limit the understanding and effectiveness of safety controls. To demonstrate the limitations of current approaches to understanding accident causation in the construction domain, the model is used to represent the findings from a recent Coronial investigation into a fatal construction incident. The benefits of applying systems thinking in accident analysis and countermeasure development by construction organisations, clients, regulators and law makers are discussed.